A Bionic Interface to Suppress the Coffee‐Ring Effect for Reliable and Flexible Perovskite Modules with a Near‐90% Yield Rate. Issue 29 (15th June 2022) - Fan, Baojin; Xiong, Jian; Zhang, Yanyan; Gong, Chenxiang; Li, Feng; Meng, Xiangchuan; Hu, Xiaotian; Yuan, Zhongyi; Wang, Fuyi; Chen, Yiwang
Abstract: The inhomogeneity, poor interfacial contact, and pinholes caused by the coffee‐ring effect severely affect the printing reliability of flexible perovskite solar cells (PSCs). Herein, inspired by the bio‐glue of barnacles, a bionic interface layer (Bio‐IL) of NiO x /levodopa is introduced to suppress the coffee‐ring effect during printing perovskite modules. The coordination effect of the sticky functional groups in Bio‐IL can pin the three‐phase contact line and restrain the transport of perovskite colloidal particles during the printing and evaporation process. Moreover, the sedimentation rate of perovskite precursor is accelerated due to the electrostatic attraction and rapid volatilization from an extraordinary wettability. The superhydrophilic Bio‐IL affords an even spread over a large‐area substrate, which boosts a complete and uniform liquid film for heterogeneous nucleation as well as crystallization. Perovskite films on different large‐area substrates with negligible coffee‐ring effect are printed. Consequently, inverted flexible PSCs and perovskite solar modules achieve a high efficiency of 21.08% and 16.87%, respectively. This strategy ensures a highly reliable reproducibility of printing PSCs with a near 90% yield rate. Abstract : The construction of a superhydrophilic bionic interface layer (Bio‐IL) significantly suppresses the coffee‐ring effect during printing of large‐area perovskite films via regulating the nucleation rate (υN ) and radial transport rate (υRT ) of the perovskite precursor, which induces a homogeneous large‐area flexible perovskite film and high‐performance inverted flexible perovskite solar cells with an efficiency of 21.08%.